2021
DOI: 10.3389/fspor.2021.694537
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Elite Female Soccer Players' Sleep, and Associations With Perceived Fatigue and Soccer Games

Abstract: The current study investigated the associations between female perceived fatigue of elite soccer players and their sleep, and the associations between the sleep of players and soccer games. The sample included 29 female elite soccer players from the Norwegian national soccer team with a mean age of ~26 years. Perceived fatigue and sleep were monitored over a period of 124 consecutive days. In this period, 12.8 ± 3.9 soccer games per player took place. Sleep was monitored with an unobtrusive impulse radio ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…Females' soccer players were found more sensitive to performance evaluation by coaches and peers [32] and more at risk for anxiety and depression than males [45] and to have shorter sleep-in comparison to other professional's sport female athletes [46]. In normal conditions, the sleep disruption is likely to be caused by the high physical and mental loads experienced during soccer games [47]. Sleep modification in normal conditions shows an association of deep and REM sleep with fatigue with increased restoring sleep two to three days after match an a pre-match reduction in sleep length [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Females' soccer players were found more sensitive to performance evaluation by coaches and peers [32] and more at risk for anxiety and depression than males [45] and to have shorter sleep-in comparison to other professional's sport female athletes [46]. In normal conditions, the sleep disruption is likely to be caused by the high physical and mental loads experienced during soccer games [47]. Sleep modification in normal conditions shows an association of deep and REM sleep with fatigue with increased restoring sleep two to three days after match an a pre-match reduction in sleep length [47].…”
Section: Discussionmentioning
confidence: 99%
“…In normal conditions, the sleep disruption is likely to be caused by the high physical and mental loads experienced during soccer games [47]. Sleep modification in normal conditions shows an association of deep and REM sleep with fatigue with increased restoring sleep two to three days after match an a pre-match reduction in sleep length [47]. Our results are also consistent with another study, who showed in Italian female professional soccer players in lockdown an increase in depressive symptoms and a sleep worsening [48].…”
Section: Discussionmentioning
confidence: 99%
“…Females’ soccer players were found more sensitive to performance evaluation by coaches and peers [ 35 ] and more at risk for anxiety and depression than males [ 52 ] and to have shorter sleep-in comparison to other professional’s sport female athletes [ 53 ]. In normal conditions, the sleep disruption is likely to be caused by the high physical and mental loads experienced during soccer games [ 54 ]. Sleep phases changes during night in an alternate way from light to deep and rem sleep [ 55 ] Sleep modification in normal conditions (not in exceptional circumstances such as lockdowns) shows an association of deep and REM sleep with fatigue with increased restoring sleep two to three days after match, a pre-match reduction in sleep length [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In normal conditions, the sleep disruption is likely to be caused by the high physical and mental loads experienced during soccer games [ 54 ]. Sleep phases changes during night in an alternate way from light to deep and rem sleep [ 55 ] Sleep modification in normal conditions (not in exceptional circumstances such as lockdowns) shows an association of deep and REM sleep with fatigue with increased restoring sleep two to three days after match, a pre-match reduction in sleep length [ 54 ]. The results of the present study are in agreement with another study, who showed in Italian female professional soccer players an increase in depressive symptoms and a sleep worsening during the lockdown [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the players train according to the various game demands in the different positions. Female football players are therefore exposed to a constant struggle to optimize the balance between the extensive load they are exposed to, and the recovery needed to keep fresh without reducing fitness ( Fullagar et al, 2015 ; Moen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%